Effects of Small Temperature Differences Detected in Callosal Circuits of the Anterior Cingulate Cortex. (21st January 2020) - Cotter, R.; Winnik, S.; Singer, A.; Aaron, G.
Highlights: Small temperature differences affect epileptic seizure propagation. Bisection of the corpus callosum in vitro reveals different seizure rates. Intact GABAB activity affects interhemispheric latency and also affects whether temperature influences seizure propagation. Abstract: We measured the sensitivity of cortical circuit activity to small differences in local cortical environments by studying how temperature affects the trajectory of epileptiform events (EEs). EEs evoked via blockade of GABA-A receptors were recorded extracellularly from mouse coronal brain slices containing both hemispheres of anterior cingulate cortex synaptically connected by corpus callosum axons. Preferentially illuminating one hemisphere with the microscope condenser produced temperature differences of 0.1 °C between the hemispheres. The relatively warmer hemisphere typically initiated the EEs that then propagated to the contralateral side, demonstrating temperature directed propagation. Severing the callosum following one hour of EEs showed that the warmer hemisphere possessed a higher rate of EE generation. Further experiments implied that intact callosal circuits were required for the increased EE generation in the warmer hemisphere. We propose a hypothesis whereby callosal circuits can amplify differences in respective hemispheric activity, promoting this directionality in seizure propagation.